1989
DOI: 10.1111/j.1600-0528.1989.tb01825.x
|View full text |Cite
|
Sign up to set email alerts
|

Per capita consumption of sugar‐containing products and dental caries in Sweden from 1960 to 1985

Abstract: The aim of the present report was to analyze sugar consumption in relation to dental caries in Sweden from 1960 to 1985. Sugar consumption is based on official statistics from the National Swedish Agricultural Board and is expressed in grams per person and day. Over this quarter-century total sugar consumption decreased approximately 5%, from 116 to 110 g/person/day. A shift occurred from direct consumption to indirect (sugar used by the food industry), the former decreasing from 76 to 50 and the latter rising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…Ericsson [1987] continues stating 'however, it appears that the propaganda against sweets can hardly be given credit for the great caries reduction since the per capita consumption of sweets and soft drinks has in creased considerably during the last decades (figure 6)'. Detailed data presented by Birkhed et al [1989] at the 'Inaugural Conference for a European Consensus Conference on Diet, Nutrition and Dental Caries' in Angers (France) in 1988 corroborated this view. At that conference, Holm and Birkhed pointed to three pieces of evidence:…”
Section: Lack Of Correlation Between the Decline Of Caries Prevalencesupporting
confidence: 59%
“…Ericsson [1987] continues stating 'however, it appears that the propaganda against sweets can hardly be given credit for the great caries reduction since the per capita consumption of sweets and soft drinks has in creased considerably during the last decades (figure 6)'. Detailed data presented by Birkhed et al [1989] at the 'Inaugural Conference for a European Consensus Conference on Diet, Nutrition and Dental Caries' in Angers (France) in 1988 corroborated this view. At that conference, Holm and Birkhed pointed to three pieces of evidence:…”
Section: Lack Of Correlation Between the Decline Of Caries Prevalencesupporting
confidence: 59%
“…There were some countries where between 1982 and 1985 the sugar consumption had increased, but where, nevertheless, regular epidemiological monitoring of caries data had shown that the caries prevalence in children continued to decrease: these were Sweden [Birkhed et al, 1989], Norway [Rølla and Øgaard, 1987], and New Zealand [König, 1990].…”
Section: Sugar Intake As a Caries Risk Factormentioning
confidence: 99%
“…, not only overcome the output independence assumption problem of HMM, but also solve the label bias problem of MEM. This model is a discriminant undirected graph model [9]. The nodes in the graph indicate the random variables, while the branches show the relationship between these random variables.…”
Section: Modelling Of Character Informationmentioning
confidence: 99%